Consciousness and education: contributions by Piaget, Vygotsky and Steiner - Stoltz, Tania; Weger, Ulrich; da Veiga, Marcelo (Frontiers in Psychology, 2024)
The objective of this study is to gain an understanding of the development of consciousness and its relationship with education based on different theoretical models—namely those by Piaget, Vygotsky and Steiner. All three of them focus on different subcomponents of the educational process and there is hence a need for integrative discussion. Piaget and Vygotsky are fundamental references in the understanding of developmental and learning processes. Steiner was a pioneer in proposing a pedagogy that progresses by integrating feeling and wanting alongside thinking in the educational process. Their theories have important similarities but also differences and these will be essential for broadening the understanding of the construction of consciousness and its relationships with education.